PNPLA3 rs1010023 Predisposes Chronic Hepatitis B to Hepatic Steatosis but Improves Insulin Resistance and Glucose Metabolism. (14th June 2017) - Pan, Qin; Chen, Mei-Mei; Zhang, Rui-Nan; Wang, Yu-Qin; Zheng, Rui-Dan; Mi, Yu-Qiang; Liu, Wen-Bin; Shen, Feng; Su, Qing; Fan, Jian-Gao
Abstract : PNPLA3 polymorphisms serve as the genetic basis of hepatic steatosis in normal population and lead to dysregulated glucose metabolism. Whether it underlies the hepatic steatosis and glucose homeostasis in chronic hepatitis B patients remains uncertain. Here, we investigated the PNPLA3 polymorphisms in biopsy-proven chronic hepatitis B patients with (CHB+HS group, n = 52 ) or without hepatic steatosis (CHB group, n = 47 ) and non-CHB subjects with (HS group, n = 37 ) or without hepatic steatosis (normal group, n = 45 ). When compared to the TT genotype, C-allele at PNPLA3 rs1010023 (CC and TC genotypes) conferred higher risk to hepatic steatosis in chronic hepatitis B patients (odds ratio (OR) = 1.768, 95% confidence interval (CI): 1.027–3.105; P = 0.045 ) independent of age, gender, and body mass index. In contrast to their role in hepatic steatosis, CC and TC genotypes of PNPLA3 rs1010023 were correlated to significant improvement of homeostasis model assessment index (HOMA-IR) as compared to TT genotype in the CHB+HS group. Downregulated fasting blood glucose also characterized the CHB+HS patients with C-allele at PNPLA3 rs1010023 (CC/TC versus TT: 4.81 ± 0.92 mmol/L versus 5.86 ± 2.11 mmol/L, P = 0.02 ). These findings suggest that PNPLA3 rs1010023 may predispose chronic hepatitis B patients to hepatic steatosis but protects them from glucose dysregulation by attenuating insulin resistance.